Crude extract from Libidibia ferrea (Mart. ex. Tul.) L.P. Queiroz leaves decreased intra articular inflammation induced by zymosan in rats - Tamires Rocha Falcão; Cássio Alexandre Oliveira Rodrigues; Aurigena Antunes de Araújo; Caroline Addison Carvalho Xavier de Medeiros; Luiz Alberto Lira Soares; Magda Rhayanny Assunção Ferreira; Roseane Carvalho Vasconcelos; Raimundo Fernandes de Araújo Júnior; Maria Luiza Diniz de Sousa Lopes; Gerlane Coelho Bernardo Guerra (BMC, 2019)
Abstract Background Libidibia ferrea (L. ferrea) has been used in folk medicine to treat several conditions and to prevent cancer. This study performed a chromatographic analysis of the crude aqueous extract of Libidibia ferrea (Mart. ex. Tul.) L.P. Queiroz (LfAE) leaves and evaluated its in vivo antioxidant and anti-inflammatory potential. Methods Polyphenols present in LfAE were characterized by high performance liquid chromatography (HPLC). Anti-inflammatory activity was studied in an experimental model of zymosan-induced intra-articular inflammation, conducted in Wistar rats treated with LfAE at the doses of 100, 200 and 300 mg/kg by gavage. Synovial fluid was collected for global leukocyte count, for spectrocopical UV/VIS analysis of myeloperoxidase (MPO) activity, total glutathione and malondialdehyde (MDA), and for quantification of inflammatory cytokines IL1-β and TNF-α by enzyme-linked immunosorbent assay. Synovial membrane was collected for histological analysis. The level of statistical significance was p < 0.05. Results HPLC detected concentrations of 1.56 (0.77) %m/m for ellagic acid and 1.20 (1.38) %m/m for gallic acid in LfAE leaves. Treatment with LfAE at all doses significantly decreased the leukocyte influx into the synovial fluid (p < 0.001) and myeloperoxidase activity (p < 0.001), an important marker of neutrophils. LfAE at doses of 100 (p < 0.05), 200 and 300 mg/kg (p < 0.001) also reduced the levels of MDA. LfAE at doses of 200 and 300 mg/kg significantly decreased the levels of IL-1β (p < 0.05) and TNF-α (p < 0.001). All doses of LfAE resulted in increased levels of total glutathione (p < 0.001). Histopathological findings confirmed a reduction of the inflammatory infiltrate in the rats treated with LfAE at a dose of 200 mg/kg (p < 0.05). Conclusion LfAE has an important anti-oxidant and anti-inflammatory effect on intra-articular inflammation.